(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
The migration and genetic drift influence the population structures, which necessitate the genetic polymorphism studies of the population subgroups. Delhi, being capital of India, has mixed population group of the individuals migrated from different parts of the country. Keeping this in view, the allelic database of Delhi population is generated here using 15 STR markers to study the impact of these natural factors (migration, genetic drift, selection etc.) on this population. For this purpose, the allelic frequencies for 15 STR loci were estimated and observed to be on higher side. Further, the study includes the calculation of observed and expected heterozygosity. Moreover, the genetic variation statistics shows that there is out breeding in this population and also the effective number of alleles is higher. The observed results indicate that all the 15 STR loci are highly polymorphic in this population which indicates that there is high degree of diversity. Also, it signifies that this is a random mating population. Moreover, it is observed that four loci (D3S1358, TH01, D13S317, and D16S539) are undergoing some sort of selection.